Biopolymers : processing and products - Niaounakis, Michael (PDL handbook series., 2015)
Biopolymers and biodegradable plastics are finding new applications in various sectors, from packaging, to medical, automotive and many more. As synthetic plastics are increasingly replaced by their bioplastic equivalents, engineers are facing new challenges including processing, costs, environmental sustainability and - ultimately - developing successful products. Biopolymers: Processing and Products, the second book of a trilogy dedicated to biopolymers, gives a detailed insight into all aspects of processing, seamlessly linking the science of biopolymers to the latest trends in the devel.